2017
DOI: 10.1002/ajmg.c.31594
|View full text |Cite
|
Sign up to set email alerts
|

Immunodeficiency in CHARGE syndrome

Abstract: Immunodeficiency can occur in CHARGE syndrome, with immunophenotypes including reduction in T‐cell counts, combined T‐B cell defects rarely requiring antibiotic prophylaxis or immunoglobulin replacement, and severe combined immunodeficiency, which is fatal without immune reconstitution. However, the prevalence of immunodeficiency in CHARGE syndrome remains unclear with few prospective studies. In this review, we examine the existing literature covering immunodeficiency associated with CHARGE syndrome, compare … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 34 publications
0
23
0
Order By: Relevance
“…They may show severe T-cell deficiency resembling SCID or, similarly to DGS, they may present transient lymphopenia, that usually normalizes over time. A close association between lymphopenia and hypocalcemia has been identified (115). Severity of the T-cell lymphopenia relates to the degree of thymic hypoplasia (127).…”
Section: Chd7 Haploinsufficiency and Charge Syndromementioning
confidence: 97%
See 1 more Smart Citation
“…They may show severe T-cell deficiency resembling SCID or, similarly to DGS, they may present transient lymphopenia, that usually normalizes over time. A close association between lymphopenia and hypocalcemia has been identified (115). Severity of the T-cell lymphopenia relates to the degree of thymic hypoplasia (127).…”
Section: Chd7 Haploinsufficiency and Charge Syndromementioning
confidence: 97%
“…Naive CD4 and CD8 lymphocytes are lower in pDGS patients compared to controls independently of age and they decline more rapidly with age (78). The improvement of the lymphopenia with age is not due to a recovery of the thymic function but to the peripheral homeostatic expansion of the available T cells, as suggested by the evidence that T cells are predominantly or almost exclusively of a memory phenotype, TRECs are low and the repertoire is oligoclonal (78,115,116). T-cell proliferation, total immunoglobulins, and specific antibody response to vaccines are typically normal.…”
Section: Digeorge Syndrome and 22q112 Deletionmentioning
confidence: 99%
“…Recent reports have demonstrated that there is a significant prevalence of immunodeficiency among CHARGE syndrome patients, which may occasionally be fatal, especially in patients who share symptoms with cDGS. 6 Choices of treatment for immunodeficiency in cDGS include stem cell transplantation, cord blood transplantation, or G-CSF-induced peripheral blood stem cell transplantation, peripheral blood lymphocyte transfusion, and thymus transplantation. Although thymus transplantation shows better survival rates (75%) 7 than others (41%), 9 it is not universally available and is not approved in Japan due to ethical issues.…”
Section: Discussionmentioning
confidence: 99%
“…These two congenital disorders are not mutually exclusive. It has been reported that the clinical manifestations sometimes overlap between CHARGE syndrome and DGS …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation